2017
DOI: 10.1002/lary.26871
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of steroid‐soaked absorbable calcium alginate nasal packing following endoscopic sinus surgery

Abstract: 1b. Laryngoscope, 128:311-316, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 34 publications
(57 reference statements)
1
47
0
Order By: Relevance
“…Recently, several trials found that bioabsorbable implants impregnated with topical steroids have beneficial effects and can reduce the incidence of these complications. 21,24,25 However, Xu et al conducted a retrospective cohort study of 142 patients who underwent ESS for CRS. They showed steroid-impregnated absorbable spacers at the middle meatal entry did not have a statistically significant reduction in postoperative synechiae formation when compared to nonabsorbable spacers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, several trials found that bioabsorbable implants impregnated with topical steroids have beneficial effects and can reduce the incidence of these complications. 21,24,25 However, Xu et al conducted a retrospective cohort study of 142 patients who underwent ESS for CRS. They showed steroid-impregnated absorbable spacers at the middle meatal entry did not have a statistically significant reduction in postoperative synechiae formation when compared to nonabsorbable spacers.…”
Section: Discussionmentioning
confidence: 99%
“…However, a steroid-soaked absorbable dressing has a better effect, which can deliver more steroids to the most difficult and unreachable areas, such as the frontal and sphenoid sinuses. 21 The clinical relevance of results regarding bioabsorbable steroid-impregnated implants following ESS was rare in the literature. Adriaensen et al reported patients with sinusband fluticasone propionate had significantly less nasal congestion compared with those patients with sinusband 60 days after surgery, 20 whereas Xu et al showed the triamcinolone-impregnated dressing did not improve the Sino-Nasal Outcome Test 20 scores compared to the saline-impregnated dressing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations